Usulan Perancangan Alat Pengering Inframerah Untuk Meminimalisir Waste Waiting Pada Proses Produksi Dental Aerosol Dengan Menggunakan Pendekatan Pengembangan Produk - Naila, Helena Dinda Putri; Suryandhini, Pratya Poeri; Oktafiani, Ayudita (Peneliti.net, 2024)
According to the Ministry of Health, after the COVID-19 situation there are still health sector challenges, namely the Triple Burden of Diases, so it is necessary to support the availability of quality medical devices to prevent these challenges from occurring. One of the companies that produce medical devices is PT. XYZ which produces dental aerosol as one of its products. Dental aerosol can play a role in facing the triple burden of diseases in preventing infectious diseases and preventing the emergence of new diseases, so that in the production process it is necessary to make efforts to prevent waste. Based on PAM data, the largest percentage is owned by NVA activities or activities that do not add value at 64%. So it is necessary to reduce waste waiting in the dental aerosol production process using the just in time approach. The results of this study can fulfill the goal of minimizing waste waiting during the assembly process that occurs in the drying process. The proposal to reduce waste waiting is to design a dryer using infrared light with the concept selection method. Based on the proposed design, there is a reduction in waste waiting time in the dental aerosol production process by 85%.